KAJIAN MINAT PEMUDA TERHADAP SEKTOR PERTANIAN DI DESA SEKARPURO KECAMATAN PAKIS KABUPATEN MALANG - Rokhmawati, Dian; Rahmawati, Mariana Fitri (Journal of Food Technology and Agroindustry dipublikasikan oleh Universitas Wiraraja, 2024)
One of the supporting pillars of the economy is the agricultural sector. Various needs in supporting food security, provision of production materials, results of industrial market strategies and sources of human resources and provision of capital for other sectors are fulfilled by the agricultural sector. This research was conducted to examine the perceptions (interests) of the younger generation in the agricultural sector in Sekarpuro Village, Pakis District, Malang Regency. This study used stratified random sampling, namely sampling based on strata. The research data was collected through questionnaires and interviews. The data analysis method used is quantitative descriptive method in the form of multiple linear regression analysis using SPSS (Statistical Package for Social Science) to analyze the effect of income, capital, family environment (parental point of view), age, education and work environment on perceptions (interest young generation towards agriculture). The research results obtained are that the interest of the young generation is strongly influenced by the parents' point of view, work environment and income. Based on the findings of a study on perceptions of youth interest in the profession of rice farming, a number of 99 young people, it is known that the interest of the younger generation in agriculture strongly agrees 4% disagrees 52.5% normal 38.4% agrees 5.1. The value of 100% is the cumulative value of the sum of 4% + 52.5 % + 38.4 %+5.1% = 100%. Meanwhile, age, capital, education did not influence the perception (interest) of the younger generation in the agricultural sector.